Perspectives on comprehensive internationalisation of higher education - Dorasamy, Nirmala (AOSIS, 2022)
This book argues that international higher education has to be competitive, sustainable and contribute to educational development both locally and internationally. It shows that higher education institutions (HEIs) are seen as being driven by an economic or an educational agenda. For example, internationalization can be influenced by the university ranking system, which is based on the international reputation of universities, the competitive quality of programmes offered in a market-oriented education environment, generation of income from the enrolment of international students, and employment of high-profile researchers. Likewise, the book contributes to the production of knowledge by positing that an international profile for HEIs is fundamental to building their international excellence, outstanding academic standards, and strengthening their competitiveness and economic growth. Although virtual internationalization can be used as an effective vehicle for students to gain international exposure, the majority of students have remained in their local environment. This book provides a detailed array of new needs, attitudes and demands that teaching and learning pedagogy has to consider with a view to fostering the internationalisation of higher education. In addition, this book also argues that HEIs must ethically and pedagogically respond to the needs of international students and other stakeholders across various modes of internationalization of higher education. The book argues that any rationale to internationalise higher education must ensure that inequitable and unethical ideologies and practices are addressed. In the same vein, this book also places emphasis on the importance of institutional quality assurance mechanisms, accreditation, learning outcomes, and multicultural connectivity through an inclusive curriculum. Lastly, in providing thorough strategies for comprehensive internationalisation of higher education, this book provides pertinent discussions on the sustainable funding models for the HEIs, repositioning the higher education sector as a vibrant export sector, reforms in higher education, governance in HEIs, entrepreneurship in higher education and competition in higher education.